Development of a Fresh Osteochondral Allograft Program Outside North America. (July 2016) - Tírico, Luís Eduardo Passarelli; Demange, Marco Kawamura; Santos, Luiz Augusto Ubirajara; de Rezende, Márcia Uchoa; Helito, Camilo Partezani; Gobbi, Riccardo Gomes; Pécora, José Ricardo; Croci, Alberto Tesconi; Bugbee, William Dick
Objective: To standardize and to develop a fresh osteochondral allograft protocol of procurement, processing and surgical utilization in Brazil. This study describes the steps recommended to make fresh osteochondral allografts a viable treatment option in a country without previous fresh allograft availability. Design: The process involves regulatory process modification, developing and establishing procurement, and processing and surgical protocols. Results: Legislation: Fresh osteochondral allografts were not feasible in Brazil until 2009 because the law prohibited preservation of fresh grafts at tissue banks. We approved an amendment that made it legal to preserve fresh grafts for 30 days from 2°C to 6°C in tissue banks. Procurement: We changed the protocol of procurement to decrease tissue contamination. All tissues were procured in an operating room. Processing: Processing of the grafts took place within 12 hours of tissue recovery. A serum-free culture media with antibiotics was developed to store the grafts. Surgeries: We have performed 8 fresh osteochondral allografts on 8 knees obtaining grafts from 5 donors. Mean preoperative International Knee Documentation Committee (IKDC) score was 31.99 ± 13.4, improving to 81.26 ± 14.7 at an average of 24 months' follow-up. Preoperative Knee Injury and Oseoarthritis Outcome Score (KOOS) score was 46.8 ± 20.9 and rose to 85.24 ± 13.9 after 24 months. Mean preoperative Merle D'Aubigne-Postel score was 8.75 ± 2.25 rising to 16.1 ± 2.59 at 24 months' follow-up. Conclusion: To our knowledge, this is the first report of fresh osteochondral allograft transplantation in South America. We believe that this experience may be of value for physicians in countries that are trying to establish an osteochondral allograft transplant program.